Pengembangan Teknologi Pembelajaran Pendidikan Agama Islam Berbasis Karakter di SMK Al-Khozini - Fitri Ayu Kurnia; Sita Acetylena (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
The purpose of this study is to explain how and what happened during the process of developing Islamic Religious Education (PAI) learning technology based on character values at Al-Khozini Vocational School. This study demonstrates that the demand for innovative learning methods, including those in PAI subjects, is growing in the current technological era. This study employs a qualitative descriptive approach to demonstrate how teachers utilize technology, including interactive media, learning applications, and digital platforms, to instill character values such as honesty, responsibility, and discipline in their students. The results of the study indicate that the use of technology in learning. In addition, the use of technology makes learning more interesting, effective, and in line with the new generation of digital education. This study recommends that the development of learning technology must continue to be carried out sustainably to support quality and character-based PAI learning. Keywords: Technology Development, Islamic Religious Education, Character.